2018
DOI: 10.1186/s13000-018-0689-9
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 diagnostic tests: a systematic literature review of scoring algorithms and test-validation metrics

Abstract: BackgroundThe programmed death receptor 1 (PD-1) protein is a cell-surface receptor on certain lymphocytes that, with its ligand programmed death ligand 1 (PD-L1), helps to down-regulate immune responses. Many cancer types express PD-L1 and evade immune recognition via the PD-1/PD-L1 interaction. Precision therapies targeting the PD-1/PD-L1 pathway have the potential to improve response and thereby offer a novel treatment avenue to some patients with cancer. However, this new therapeutic approach requires reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(132 citation statements)
references
References 34 publications
2
128
0
2
Order By: Relevance
“…Quantification of PD‐L1 expression in patients with advanced NSCLC is useful for predicting the response to immunotherapy with checkpoint inhibitors that disrupt the PD‐1/PD‐L1 interaction . Two commercially available PD‐L1 IHC assays, the PD‐L1 IHC 22C3 pharmDx and the Ventana PD‐L1 SP263 assays, have been shown to be highly concordant in quantifying PD‐L1 expression regardless of the TPS cutoff levels or sample type (surgical resections/biopsies vs cytological specimens) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification of PD‐L1 expression in patients with advanced NSCLC is useful for predicting the response to immunotherapy with checkpoint inhibitors that disrupt the PD‐1/PD‐L1 interaction . Two commercially available PD‐L1 IHC assays, the PD‐L1 IHC 22C3 pharmDx and the Ventana PD‐L1 SP263 assays, have been shown to be highly concordant in quantifying PD‐L1 expression regardless of the TPS cutoff levels or sample type (surgical resections/biopsies vs cytological specimens) …”
Section: Discussionmentioning
confidence: 99%
“…The Dako platform (Agilent Technologies/Dako, Carpinteria, CA, USA) has developed the 22C3 and 28‐8 antibodies in conjunction with pembrolizumab and nivolumab. The Ventana platform (Ventana Medical Systems Inc, Tucson, Arizona) has developed the SP142 and SP263 antibodies in conjunction with atezolizumab and durvalumab . Several clinical trials have demonstrated great heterogeneity in the cutoff levels and methods used for PD‐L1 testing and the assessment of PD‐L1 positivity based on the various assays …”
Section: Introductionmentioning
confidence: 99%
“…Tumor‐infiltrating immune cells (TIICs), whose function and composition subtly altered according to the immune status of the host, have been reported to be effectively targeted by drugs and to correlate with the clinical outcome . Mechanism studies confirmed that between TIICs and malignant cells in the tumor stroma, there is in fact a complex interaction which has significant prognostic relevance as the immune system has a dual role by supporting both host defense and tumor progression .…”
Section: Introductionmentioning
confidence: 99%
“…63 Furthermore, multiple different assays and different staining protocols may yield different outcomes, particularly with regard to the percentage of tumor cells expressing PD-L1 and whether PD-L1 expression in the microenvironment is taken into consideration. 64,65 Moreover, because PD-L1 can induce early T cell proliferation, it is possible that in certain instances, PD-L1 expression will actually be beneficial. 62 Finally, based on recent data in NSCLC, it is likely that some mAbs targeting the PD-1 pathway are dependent on PD-L1 expression while other are not.…”
Section: Predicting Treatment Responsesmentioning
confidence: 99%
“…Additionally, core/fine needle aspiration biopsies used for analysis may not be representative of PD‐L1 expression levels in the tumor as a whole . Furthermore, multiple different assays and different staining protocols may yield different outcomes, particularly with regard to the percentage of tumor cells expressing PD‐L1 and whether PD‐L1 expression in the microenvironment is taken into consideration . Moreover, because PD‐L1 can induce early T cell proliferation, it is possible that in certain instances, PD‐L1 expression will actually be beneficial .…”
Section: Introductionmentioning
confidence: 99%